2017
DOI: 10.1021/acscatal.7b01124
|View full text |Cite
|
Sign up to set email alerts
|

Low-Overpotential Electroreduction of Carbon Monoxide Using Copper Nanowires

Abstract: We report on Cu nanowires as highly active and selective catalysts for electroreduction of CO at low overpotentials. The Cu nanowires were synthesized by reducing pregrown CuO nanowires, with the surface structures tailored by tuning the reduction conditions for improved catalytic performance. The optimized Cu nanowires achieved 65% faradaic efficiency (FE) for CO reduction and 50% FE toward production of ethanol at potentials more positive than −0.5 V (versus reversible hydrogen electrode, RHE). Structural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
159
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(167 citation statements)
references
References 37 publications
8
159
0
Order By: Relevance
“…A few recent studies have reported high selectivity for direct CO 2 R to methanol (47-49), and further evaluation may yield valuable design principles for electrocatalytic systems that can accomplish a direct synthesis. Alternatively, a number of recent studies have reported high selectivity for direct CO 2 R and carbon monoxide reduction (COR) to ethanol, and lower but nonnegligible selectivity to n-propanol (50)(51)(52)(53)(54)(55).…”
Section: Direct Electrochemical Conversion Of Co 2 To Alcoholsmentioning
confidence: 99%
“…A few recent studies have reported high selectivity for direct CO 2 R to methanol (47-49), and further evaluation may yield valuable design principles for electrocatalytic systems that can accomplish a direct synthesis. Alternatively, a number of recent studies have reported high selectivity for direct CO 2 R and carbon monoxide reduction (COR) to ethanol, and lower but nonnegligible selectivity to n-propanol (50)(51)(52)(53)(54)(55).…”
Section: Direct Electrochemical Conversion Of Co 2 To Alcoholsmentioning
confidence: 99%
“…Polycrystalline Cu also results in the exposure of high index facets which also show increased selectivity for C2+ products. [23][24][25][26][27] XRD patterns ( Figure 1d conditions. During this period of time EIS measurements were taken to determine the cell resistance, and it was found over the course of an hour that the OCV typically changed from -0.2 V to -1.0 V, while the cell resistance reduced from ~30 Ω to ~4 Ω at equilibration due to wetting of the anion exchange membrane ( Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Since the reported CVs for example for Cu(1 0 0) differ strongly one from another (see Figure ). Therefore a direct comparison of the CVs recorded on complex Cu(poly) materials with literature data of Cu( hkl ) is not straightforward …”
Section: Discussionmentioning
confidence: 99%